Thoracophagus conjoint twin in Orang Asli - HTAA experience - Abdullah, Suhaiza; Roslani, Annaliza; Abd. Aziz, Azian; Chin, Choy Nyok (2010)
Conjoint twin is one of recognized extreme complications of monochorionic twin pregnancy.Advancement of radiological modalities and techniques allows assessment of fetal internal organs which can make detection of abnormality and early diagnosis possible. High-end ultrasonography(US)complimented by Magnetic Resonance Imaging(MRI)are currently used for this purpose hence allowing early planning,intervention and mode of delivery.We illustrate a case of conjoint twin in a young Orang Asli who presented with thoracophagus conjoint twin. Antenatal MRI was used to asses the degree of fusion.